4-Benzyl-7-chloro-2H-1,4-benzoxazin-3(4H)-one - Li, Zhu-Bo (International Union of Crystallography, 2009)
In the title compound, C(15)H(12)ClNO(2), the two benzene rings are nearly perpendicular to each other [dihedral angle = 89.99 (13)°]. The O atom of the six-membered heterocyclic ring is disordered over two sites in a ratio of 0.46 (4):0.54 (4) and is displaced from the mean plane formed by other five atoms, resulting an envelope conformation of the six-membered hetercycle ring.